Atrial fibrillation is associated with increased mean platelet volume in patients with type 2 diabetes mellitus. (September 2013) - Turgut, Okan; Zorlu, Ali; Kilicli, Fatih; Cinar, Ziynet; Yucel, Hasan; Tandogan, Izzet; Dokmetas, Hatice Sebila
<x xml:space="preserve">Abstract</x> Platelet abnormalities in diabetes mellitus (DM) and atrial fibrillation (AF) may underline the etiology of a prothrombotic state in these conditions. Increased mean platelet volume (MPV) is a marker of abnormal platelet function and activation. We aimed to investigate the possible association of chronic AF with MPV in patients who have type 2 DM. Patients who had type 2 DM with either chronic (≥6 months) AF or normal sinus rhythm (NSR) were included in the study. A total of 162 patients (aged 38–89 years) were divided into 2 groups according to the presence of either AF or NSR. Group 1 consisted of 81 diabetic patients with AF, and group 2 consisted of 81 diabetic patients with NSR. The two groups were not significantly different in terms of age, and gender, as well as in hypertension, smoking, history of coronary artery disease, previous cerebrovascular accidents, microalbuminuria, retinopathy, duration of DM, body mass index, hemoglobin A1c, total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and triglyceride (p > 0.05 for all variables). Although no significant difference was present between groups concerning platelet count; for patients with AF, MPV was higher compared with patients with NSR (9.0 ± 0.2 fl vs. 8.4 ± 0.2 fl; p = 0.001). Furthermore, no significant difference was noted between groups regarding routine medications received by patients. In multivariate logistic regression analysis, MPV was the only variable independently related to AF (OR = 2.659; 95% CI, 1.286–5.498; p = 0.008). Consequently, it is concluded that AF is associated with increased MPV in patients with type 2 DM, suggesting the presence of tentatively related processes leading to reciprocal interaction.